ชาคำฝอย - วงษ์ใหญ่, วาสนา (RMUTSB ACADEMIC JOURNAL, 2013)
ชาคำฝอยจัดเป็นชาสมุนไพรผลิตจากกลีบดอกคำฝอย มีคุณสมบัติ ลดความดันโลหิต ลดไขมันในเส้นเลือดและช่วยให้ระบบโลหิตหมุนเวียนดี สำหรับกลีบดอกคำฝอยที่ใช้ผลิตชานั้นมีสีส้มเหลือง สีส้มหรือสีส้มแดง ที่มีเม็ดสีที่ให้สารสีเหลือง (carthamidin) ละลายในน้ำและสารสีส้ม (carthamin) ละลายในด่าง กลีบดอกคำฝอยประกอบด้วย โปรตีน ไขมัน เซลลูโลส แซคคาไรด์ และธาตุอาหาร เช่น สังกะสี เหล็ก ทองแดง แมกนีเซียม อะลูมิเนียม แคลเซียม และซีลีเนียม เป็นต้น Safflower tea Safflower tea is a natural herbal product using for reducing blood pressure, cholesterol, preventing atherosclerosis, and improving blood circulation system. Safflower florets have yellow – orange, orange and red – orange colors used for safflower tea. These floret colors have a yellow pigment of carthamidin which is water soluble yellow dye and a red pigment of carthamin which is readily soluble in alkali. In addition, the composition of safflower florets are protein, lipids, cellulose, saccharides and minerals such as Zn, Fe, Cu, Mg, Al, Ca and Se.